Practical report: Sarawak Foundation / Siti Nurul Hazlinda Ahmad Sulaiman Shah - Ahmad Sulaiman Shah, Siti Nurul Hazlinda (Universiti Teknologi MARA, Sarawak, 2013)
Sarawak Foundation has been established in 27 May 1971 by Sarawak Government which been ruled by Yang Berhormat Datuk Patinggi Haji Abdul Rahman Ya’kub at that time. Many initiatives have been taken in order to ensure that Sarawak Foundation can be operated efficiently and effectively to help people of Sarawak. Datuk Amar Abang Haji Yusuf Puteh was the first Director in Sarawak Foundation. Sarawak Foundation been established to provides and develop education facilities in Sarawak. It is also to nourish the solidarity and loyalty in people of Sarawak. Sarawak Foundation have been managed by Lembaga Amanah consisted of Chairman which have been appointed by Governor and along with other four members which appointed by Chief Minister during its earlier establishment.